Excess Commuting in the US: Differences between the Self-Employed and Employees - J. Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute for the Study of Labor (IZA), 2015)
In this paper, we propose a new spatial framework to model excess commuting of workers and we show empirical differences between the self-employed and employees in the US. In a theoretical framework where self-employed workers minimize their commuting time, employees do not minimize their commuting time because they lack full information, and thus the difference between the time devoted to commuting by self-employed workers and employees is modeled as wasteful commuting (i.e., excess commuting). We first formulate a microeconomic framework for commuting by modeling the location of individuals in urban cores surrounded by rings. Using the American Time Use Survey for the years 2003-2013, our empirical results show that employees spend twelve more minutes per day, or forty percent of the average commuting time, compared to their self-employed counterparts. This is consistent with our "diana" model, in that location is an important factor.
Keywords: R20; R41; J64; 330; excess commuting; urban cores; American Time Use Survey; self-employed workers; employees